Dimensional changes in height of labial alveolar bone of proclined lower incisor after lingual positioning by orthodontic treatment: A cephalometric study on adult Bengali population - Amit Shaw (Wolters Kluwer Medknow Publications, 2015)
Aim: The study aims to know whether modern orthodontic treatment procedure do actually cause permanent bone loss at the alveolar bone crest or improve alveolar bone morphology on labial aspect of permanent incisors which are to be moved lingually. Settings and Design: manual tracings of pre and post treatment lateral cephalometric radiographs were used. Material and Method: The cephalometric radiographs of 34 adult bengali subjects whose orthodontic treatment involved lingual positioning of procumbent mandibular central incisors were examined to determine the morphologic changes (bone height) in the labial alveolar bone that resulted from orthodontic treatment. Result: Comparison of tracings of radiographs taken before and after treatment indicated that 57.6% shows an increase in labial alveolar bone height, 30.3% shows decreased value and 12.1% shows no change with the decrease in the angulation between long axis of lower incisor and mandibular plane (GoGn). In the increase group there is a significant increase in the distance 'incisal edge to D point' whereas this dimension decreased significantly in the rest of the cases. In addition, a significant positive correlation (r = 0.56) was found between the changes in the distance from the incisal edge to the 'D' point and the alveolar bone height. But no significant relation was found between alveolar bone height and decrease in angulation of lower incisor either in the 'increase group' (r = 0.13, p > 0.05) or in the 'decrease group' (r = 0.37, p > 0.05). Conclusion: These findings indicate that during orthodontic treatment that involves lingual positioning of procumbent teeth but no intrusion, an increase in the amount of buccal alveolar bone may take place.